The origin of Kaingang baskets: the symbolic repertoire in the field of visuality applied to indigenous basketerie - Pantu , João Natalino; Kaingang, Tadeu dos Santos; Souza , Sheilla P. Dias de (Farol, 2022)
This article presents studies on Kaingang basketeries and paintings in Kaingang baskets by pairs of Kaingang teachers together with artists, teachers and students from the Visual Arts course at UEM. Interdisciplinary methodological references were use, associating research in visual poetics, autoethnography and ethnohistory. The results unfold in the production of articles also made by the other pairs of project participants which contribute to the dissemination of aspects of indigenous art, subsidizing the practice of art teachers.